Parallelizing model checking algorithms using multi-core and many-core architectures - Wu, Zhimin (2017)
The reliance on the functioning of software systems is growing with the development of IT industry. The complexity and scalability to design these systems are increasing, especially for concurrent systems with concurrent executions, communications and resource distributions, e.g., classical cryptography protocols and quantum communication systems. Thus, the reliability of these systems becomes crucial. Model checking is an automated verification approach to validate these complicated systems, which has been proved to be effective in discovering errors.